Academic nations in China and Japan : framed in concepts of nature, culture and the universal - Sleeboom-Faulkner, Margaret, 1961- (Nissan Institute/Routledge Japanese studies series., 2004)
Chinese and Japanese people's descriptions of themselves and each other differ vastly and contrast starkly with Western perceptions. This book explores human categories and how academics classify themselves and the world.